Límites a la docencia en los servidores y funcionarios públicos - Hurtado Magán, Giovana (2021)
The Political Constitution of Peru establishes that public servants in general cannot receive double remuneration or income from the State; furthermore, with respect to certain officials, it points out the incompatibility of the exercise of other public or private activities, empowering only the exercise of the teaching function. The hiring of civil servants as teachers in Public Administration institutions is frequently carried out through the mechanisms that the State Contracting Law empowers; however, this norm indicates various incompatibilities to be a participant, bidder or contractor in the selection processes. Through a hermeneutical analysis methodology, we are going to analyze the norms that establish limitations and empower the teaching practice of public servants in general, as well as judges, prosecutors, congressmen, members of the National Board of Justice and the National Jury. of Elections.